2016
DOI: 10.1002/cbf.3213
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐24‐3p enhances cell growth in hepatocellular carcinoma by targeting metallothionein 1M

Abstract: Dysregulation of microRNAs has been demonstrated to contribute to malignant progression of cancers, including hepatocellular carcinoma (HCC). MiR-24-3p was previously reported to be significantly upregulated in HCC. However, the potential role and mechanism of action of miR-24-3p in the initiation and progression of HCC remain largely unknown. Quantitative reverse transcription polymerase chain reaction demonstrated that miR-24-3p was significantly upregulated in HCC tumor tissues compared with nontumor tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 29 publications
3
25
1
Order By: Relevance
“…To further explore the exactly regulated process of CASC2 in HCC, it was inferred that miR‐24‐3p may be the downstream target of CASC2 based on the published studies and bioinformatic analysis. Emerging studies indicated that miRNA, belongs to ncRNA, is also plays a crucial role in human HCC, including miR‐24‐3p . MiR‐24‐3p was up‐regulated in HCC tissues and serum, and promoted cell growth, which was correlated with poor prognosis of patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore the exactly regulated process of CASC2 in HCC, it was inferred that miR‐24‐3p may be the downstream target of CASC2 based on the published studies and bioinformatic analysis. Emerging studies indicated that miRNA, belongs to ncRNA, is also plays a crucial role in human HCC, including miR‐24‐3p . MiR‐24‐3p was up‐regulated in HCC tissues and serum, and promoted cell growth, which was correlated with poor prognosis of patients .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies indicated that miRNA, belongs to ncRNA, is also plays a crucial role in human HCC, including miR‐24‐3p . MiR‐24‐3p was up‐regulated in HCC tissues and serum, and promoted cell growth, which was correlated with poor prognosis of patients . The direct or indirect modulation of miRNA by lncRNA is one of the important mechanisms to exert it biological function.…”
Section: Discussionmentioning
confidence: 99%
“…Ding J, et al reported that low MT1M expression correlated with tumor recurrence and disease-free survival [33]. Dong X, et al reported that MT1M was downregulated in HCC tumor tissues significantly and miR-24-3p/MT1M pathway may contribute to the initiation and progression of HCC [34]. Ji XF, et al reported that MT1M promoter methylation was significantly increased in HCC group and was positively correlated with HCC tumor size [35].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR‐24 and miR‐509 were significantly regulated in CAP‐mAb‐miR‐3074. miR‐24 is a well‐known proliferation enhancing oncogenic miRNA playing a crucial role in many different cancers (Chen et al, ; Dong et al, ; Hiller, Ovalle, Gagnon, Curran, & Wang, ; Zhang, Duan et al, ). In addition, miR‐509 has been shown to have anti‐proliferative effects in different cell lines (Wang et al, ; Wang, Deng, & Fu, ; Zhang, Liu, Han, Wang, & Yang, ).…”
Section: Discussionmentioning
confidence: 99%